B106 Quadratus lumborum blockas surgical anesthesia for high-risk major abdominal surgery. (11th August 2022) - Beh, ZY; Mok, CS; Lim, WL; Yip, HH; Loh, PS; Ramli, MAS; Omar, SZ
Abstract : Background and Aims: Quadratus lumborum (QL) block has been described as regional analgesia techniques in various abdominal surgeries and majority published as case reports with a few randomized controlled studies. However, current available literature described the use of QL block for post-operative analgesia to date.We present the first case report of using QL block as surgical anesthesia for a high-risk major abdominal surgery. Methods: Case presentation: A 29-year-old lady with underlying osteogenesis imperfecta type 3 with severe kyphoscoliosis, severe restrictive lung disease (lung function test: forced expiratory volume in 1 second, FEV1 0.36 liter; forced vital capacity, FVC 0.44 liter; FEV1/FVC 81%), cervical syringomyelia with cranio-cervical junction stenosis (C2/C3) and wheelchair bound. She has bilateral large multi-loculated ovarian cyst (CT scan showed right side: 12.1 x 9.3 x 10.3cm; left side: 6.8 x 9 x 7cm) which is singnificantly impairing her respiratory function. The patient and her family is keen on surgical intervention despite being informed that general anesthesia is extremely high-risk for her during the multidisciplinary meetings. She has limited anesthetic options with possibility of abandoning the surgery if unable to provide surgical anesthesia with proposed anesthetic techniques – neuraxial anesthesia as the first-choice to be supplemented with truncal block, multimodal analgesia. However, neuraxial anesthesia under ultrasound guidance and experienced hands was unsuccessfully attempted. Patient safely underwent lower midline laparotomy, ovarian cystectomy under ultrasound guided bilateral QL block with monitored sedation. Results: Conclusions: This is the first published case describing the use of QL block as surgical anesthesia for a high-risk abdominal surgery with multi-modal analgesia approach.